Financing Channels, Innovation Investment and Innovation Sustainability - Wenjing Li (Forest Chemicals Review)
Innovation sustainability is of great significance for enterprises to build dynamic competitive advantages, but how to motivate enterprises to innovate continuously is still a key question that academic circles are eager to answer. Technological innovation largely depends on the amount of external financing that enterprises obtain, and maintaining innovation sustainability depends on the long-term investment of innovation funds. How to form a reasonable financing structure through the effective allocation of financial resources is not only related to the performance of financial functions, but also related to the sustainability of enterprise innovation. Therefore, it is of great significance to accurately identify the financing channels of innovation of Chinese enterprises for improving the financing environment and enhancing the innovation ability of enterprises. Based on the 2009-2019 panel data of listed companies in China’s strategic emerging industries, I use the expansion model of Euler’s equation to empirically study the relationship between financing channels, innovation investment and innovation sustainability. The study finds that internal cash flow and equity financing are the main financing channels for innovation investment in strategic emerging industries. Both commercial credit and informal channel funds have no impact on innovation investment. Debt financing has not only failed to promote technological innovation of enterprises, but on the contrary restricted the investment in technological innovation. When the main financing channels fluctuate, listed companies in strategic emerging industries maintain innovation sustainability through the smoothing effect of cash holdings. Through firm heterogeneity analysis, it is found that young companies and companies with severe financing constraints rely more on the smoothing effect of cash holdings than other firms.